National Culture and Union Membership: A Cultural-Cognitive Perspective - A. Posthuma, Richard (Relations industrielles / Industrial Relations, 2009)
SummaryNational Culture and Union Membership: A Cultural-Cognitive PerspectiveMoving beyond the normative and regulative perspectives of neo-institutional theory, this study adopted a cultural-cognitive perspective to study the influence of multiple dimensions of national culture on union membership. Cultural frameworks were compared using data from the World Values Survey that were matched to GLOBE and Hofstede national culture scores (n = 43,867 employees, 32 countries). Contrasts between GLOBE and Hofstede scores revealed that GLOBE culture constructs were better predictors and they also enabled an improved understanding of the relationships between national culture and union membership. This resolved the paradoxical lack of a significant relationship between collectivism and union membership in prior research. Specifically, union membership was positively related to institutional collectivism but not to in-group collectivism. Also, that fact that GLOBE Performance Orientation was negatively related to union membership explained why Hofstede’s Masculinity was negatively related to union membership in prior research. Moreover, prior research on union membership tended to use either individual level (i.e., employees) variables, or macro level (i.e., country) variables to explain union membership. Recently developed statistical techniques enabled the analysis of both individual and country level variables in a hierarchical model. Results show that union membership was positively related to sex (female), education, and institutional collectivism, and negatively related to occupation (supervisors and professionals) and performance orientation. There were curvilinear relationships between union membership and age and uncertainty avoidance. Younger and older people were less likely to be union members. Low or high uncertainty avoidance increased union membership. The juxtaposition of the influences of Age and Uncertainty Avoidance on union membership revealed an interesting phenomenon. Opposing curvilinear relationships (concave vs. convex), suggested a complex yet interrelated relationship between age and uncertainty avoidance that is worthy of future research. At different ages people may use uncertainty avoidance differently to evaluate the risks and benefits of union membership.